Integrated education in Kerala: the pioneering role of Sayyed Ismail Shihabuddin Pookkoya Thangal of Panoor (1936-2010) / Mohd. Noh Abdul Jalil and Sayyed Mohamed Muhsin - Abdul Jalil, Mohd. Noh; Muhsin, Sayyed Mohamed (Academy of Contemporary Islamic Studies (ACIS), 2021)
This paper aims at analysing the concept of integrated education and its implementation by Sayyed Ismail Shihabuddin Pookkoya Thangal of Panoor in Kerala, India. The scholar ardently advocated the importance of integrated education. He established educational institutions and spearheaded them till the end of his life. He believed that integrated education is instrumental in fulfilling the duties of a Mu’min (true believer) in this world, i.e., Khilāfah (vicegerency), ʿubūdiyah (servitude) and amānah (trust). In addition, He thought that due to various reasons, Islam is misunderstood and misrepresented in the modern world, which could only be rectified with proper da’wah works imbued with al-ḥikmah (wisdom). These works can only be done after Muslims profoundly mastering both Islamic and human sciences. This paper employs textual studies of relevant literature produced by Sayyed Ismail, followed by an analysis of its impacts on society. This paper found that Sayyed Ismail could be regarded among the first in Kerala who put forth the idea of education that integrates the Islamic sciences (Naqli knowledge) and the rational sciences (Aqli knowledge) with an aim to produce Muslims who can efficiently deal with the needs and challenges of the modern world.